Assessing Trends in Access and Success at the Gert Sibande TVET College, South Africa - Mwale, Bongani June; Ntsobi, Mfanelo (An Overview of Literature, Language and Education Research Vol. 2, 2024)
The aim of this study was to assess trends in access and success at the Gert Sibande TVET College during the sample period 2010-2020. The objectives of the study were to assess trends in total headcount enrolments; trends in proportions of headcount enrolments and; trends in completion or certification rates in Report 191 N3, Report 191 N6 and NC (V) Level 4 programmes during 2010-2020. The factors analysed in the study were thus: total headcount enrolment; gross enrolment ratio and; completion or certification rates for all programmes during the 2010-2020 period. The study employed a quantitative methodology. A descriptive approach was applied in this research study, and data was analyzed mainly using trend analysis of headcounts over time and descriptive statistics, particularly average annual growth and certification rates. The key findings were that total enrolments grew by an average annual growth of 8.4%, and mainly consisted of Black Africans and female students during the period under review. Certification rates in the Report 191 N3 programme demonstrated good progress regarding student success during 2016-2018. Despite the decline in 2017, certification rates in Report 191 N6 business studies recorded good performance over the period under review, while certification rates in Report 191 N6 engineering studies programme were considerably poor. Certification rates in NC(V) level 4 programme waned during 2012-2016, despite recoveries during 2017-2019. In general, student success at the College was quite volatile, suggesting the need to implement measures for improvement. The delivery modalities of programmes are still predominantly traditionally lecturer-centred, and there is limited use of technology for blended learning approaches. The few colleges making use of distance provision still use the traditional correspondence paper-based model, which does very little to support student success, and has been associated with poor success rates.